Seleção de fungos e otimização de meio de cultura para a produção de ácido oxálico visando à solubilização de rocha fosfática - Amaro, Jeniffer Kelly Cortes (2020)
A biotechnological strategy for the production and application of oxalic acid aiming to solubilize phosphorus from rock phosphate (RF) is described in this work. Six fungal species and three culture media were evaluated to maximize oxalic acid production. The fungal isolate and the culture medium that stood out for oxalic acid production were Sclerotium rolfsii and Tsao medium. The conditions of Tsao medium were optimized following response surface methodology after an initial screening of factors with significant effect on RF solubilization. The optimized levels of factors were 1 g L-1 NaNO3; 100 g L-1 glucose; 2 g L-1 KH2PO4, 4.5 g L-1 yeast extract, 25 mg L-1 MgSO4.7H2O; 20 days of incubation. With this combination, 75 mmol L-1 oxalic acid was obtained, increasing by 3 times the production in non-optimized condition (25 mmol L-1). In addition, it was found that for S. rolfsii the addition of Mn and pH buffering had no effect on oxalic acid production. A solubilization of 100% of the P contained in the low solubility RF was achieved using oxalic acid produced by S. rolfsii. Thus, the use of S. rolfsii to produce oxalic acid appears as a promising alternative for phosphorus solubilization from RF. Keywords: phosphorus; microorganisms; oxalate; phosphate rock.